PERSEPSI MASYARAKAT TERHADAP KEBIJAKAN TRANS KOETARADJA PADA KORIDOR PUSAT KOTA – MATA IE DAN PUSAT KOTA – AJUN – LHOKNGA MENGGUNAKAN INDIKATOR VARIABEL LATEN - Muhammad Merfazi; Sugiarto Sugiarto; Renni Anggraini (Prodi Magister Teknik Sipil Unsyiah, 2019)
Community dependence on private transportation modes is a major factor in congestion in Banda Aceh. For this reason, the Aceh government implemented the operation policy of Trans Koetaradja to reduce the impact of congestion. Community perception is one of the important aspects in policy making, because by involving the community, decision makers will be able to capture the views, needs and expectations of the community. The purpose of this study is to examine public perceptions of the Trans Koetaradja policy as a case study at 2 (two) corridors, City Center - Mata Ie and City Center - Ajun - Lhoknga. The data collection method used was Stated Preference (SP) with a total of 220 respondents by stratified random sampling. The SP questionnaire contains information about socio-economic, travel behavior, and respondents' perceptions. The result of perception showed that all psychological questions had a good value above 2.5 (average) which was 2.81 (70.20%) from the reference of the 1-4 Likert scale with the indicator with the highest level of acceptance of 3.32 that was a private vehicle needed in everyday life. Data processing and analysis used the Multiple Indicators Multiple Causes (MIMIC) model which was one of the branches of Structural Equation Modeling (SEM), the regression parameters calibrated using Lisrel 9.3 software to produce a measurement model that was the perception of